Deconstructing Ideals of Worship with Children - van Leersum-Bekebrede, Lydia (Studia liturgica, 2019)
In most congregations, children participate in worship in various ways. In this article we pose the question: how can we describe and understand the variety in practices of worship with children? The case we consider is the Protestant context in the Netherlands. Archival research shows that since the introduction of differentiated worship for children, tension has arisen between worship with the entire congregation and worship aimed specifically at children. This tension between intergenerational worship and target-group worship persists; while most liturgists and youth work professionals argue for intergenerational worship, some defend the merits of target-group worship. However, in this ethnographic research we indicate that the portrayal of intergenerational worship as the ideal, and target-group worship as its opposite, or vice versa, leaves much of the normativity in worship with children hidden. We, therefore, deconstruct ideals of worship with children to open up other ways of understanding the variety of worship with children. In doing so, we argue that pedagogical and theological normativity influence worship practices in complex ways. Future research may advance this investigation by focusing on adults' and children's roles in shaping worship practices and exploring the theological implications of these practices in more depth and detail.